2018
DOI: 10.22159/ajpcr.2018.v11i6.25522
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Stability Assessment of Arabica and Civet Coffee Extracts Based Cosmetic Preparations

Abstract: Objective: The coffee is one of the most common beverages with reported health benefits. The coffee extracts are used in cosmetic and pharmacological preparations. The present study deals with the development of Arabica and Civet coffee extract based cosmetic formulas and its stability.Methods: Coffee extracts were prepared by mechanical pressing and solvent extraction methods. The total phenolic content of the extracts was assessed by Folin-Ciocalteu colorimetric method. The body lotion (BL) and hand moisturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This role is performed by occlusive substances, including hydrocarbons, stearic acid, linolenic acid, and sterols, commonly found in plants oils. The coffee bean has been extensively investigated as a natural ingredient in moisturizing cosmetics due to its rich oil composition and antioxidant activity (Pereda et al, 2009;Chaiyasut et al, 2018;Diamantino et al, 2019;Putri et al, 2019). However, recent studies also demonstrated the effectiveness of hydro-alcoholic extracts of coffee silverskin as an occlusive agent (Rodrigues et al, 2016b,d).…”
Section: Hydration (Persoc: Condition)mentioning
confidence: 99%
“…This role is performed by occlusive substances, including hydrocarbons, stearic acid, linolenic acid, and sterols, commonly found in plants oils. The coffee bean has been extensively investigated as a natural ingredient in moisturizing cosmetics due to its rich oil composition and antioxidant activity (Pereda et al, 2009;Chaiyasut et al, 2018;Diamantino et al, 2019;Putri et al, 2019). However, recent studies also demonstrated the effectiveness of hydro-alcoholic extracts of coffee silverskin as an occlusive agent (Rodrigues et al, 2016b,d).…”
Section: Hydration (Persoc: Condition)mentioning
confidence: 99%
“…The product was stable and did not change in color, odor, and texture for three months at 40 ° C. Body lotion was found to be uncontaminated with lead, Traditional Medicine Journal, 26(3), 2021 whereas arsenic and mercury were found in negligible amounts and were shown to be safe free of pathogenic microbes. The coffee extracts in the product nourished and protected the skin and were suitable for topical applications (Chaiyasut et al, 2018).…”
Section: Coffee Formulation As Moisturizer and Skin Nutritionmentioning
confidence: 99%
“…to increase attractiveness, protect, and repair for better appearance (Haynes et al, 1997). The use of coffee in cosmetic were developing, mainly as antiaging (Girsang et al, 2020;Safrida et al, 2017), antioxidant (Yanni et al, 2018;Sunoqrot et al, 2021;Zainol et al, 2020), sunscreen (Riberio et al, 2013;Rodrigues et al, 2016;Marto et al, 2016), moisturizer (Handayani et al, 2020;Chaiyasut et al, 2018), anti-cellulite (Herman et al, 2013), and face brightener (Kiattisin et al, 2016;Seo et al, 2019). The ethanol extract of arabica coffee beans had a very strong antioxidant is with an IC50 value of 12.43 ppm (DPPH assay)) (Ajhar and Meilani, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation